Epigraph a novel - Lish, Gordon (Four Walls Eight Windows, 1996)
A series of letters written by a husband to the women volunteers who looked after his wife in her dying days. They begin as polite thank you notes, but gradually deteriorate into insults. A look at the anger, self-pity, even madness, that grief can engender.